Mechanisms and Application of Fruit and Vegetable Shelf Life Extension Using 1-MCP, NO, and Melatonin: Systematic Review - Melati Pratama; Daniel Saputra; Gatot Priyanto; Anny Yuniarti (The University of Lampung, 2025)
Fruits and vegetables are perishable commodities after harvest. Fruit and vegetable damage occurs due to post-harvest metabolic processes that can result in the formation of ROS and ethylene, bacteria, fungi, chilling injury and mechanical damage (wounds). New technologies were discovered to inhibit ripening, aging and post-harvest fruit damage, namely the use of Methylcyclopropene (MCP), Nitric Oxide (NO) and Melatonin. The purpose of this paper is to analyze the mechanism of the three inhibitors, their applications, advantages and disadvantages so that they can be used effectively and efficiently. The method used is systematic review, data are collected and analyzed systematically. A review of 106 articles shows that MCP, NO, and melatonin have different mechanisms. MCP works by inhibiting ethylene receptors, NO through four pathways (S-nitrosylation, limiting SAM formation, forming MACC, binding NO-ACC-ACC), and melatonin through four pathways (slowing ripening, reducing cold damage, as an antioxidant, as an antibacterial agent).